Teknik Budidaya Rumput Laut dengan Metode Rawai - Nasrun, Muhammad; Bijaksana, A.Muh.Arif; Fatmawaty, A.St. (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2024)
To determine the potential, cultivation techniques, and the amount of income received by seaweed farmers in the Bahari beach area by applying the seaweed cultivation technique of the rawai method is the purpose studies. Quantitative methods were used in this research through a descriptive approach. The overall population consisted of 4 farmer groups where each group consisted of 10 members who joined, with purposive sampling techniques taken samples of 2 farmer groups or 20 people used as respondents. Using primary-secondary data types, the results of observations, interviews, documentation and questionnaire filling are the primary data of the study. Records of the results of previous research both from agencies related to the research studied are data secondary. Based on research result, cultivation techniques are used with the Rawai method where seaweed management begins with the manufacture of planting equipment consisting of ropes, bamboo, sterofom to anchors, then seed preparation, planting and maintenance until the age of the seaweed is ready for harvest. This technique is quite effective because it provides benefits where the amount of profit obtained by farmers on the coast of Bahari beach is Rp. 396,029,148.